Managing human resources for the Millennial generation - Sauser, William I.; Sims, Ronald R. (Contemporary human resource management., 2012)
The purpose of this book is to explore the talents, work styles, attitudes, and issues that members of the Millennial generation are bringing with them as they enter the workforce. The Millennial generation is a roughly 20-year cohort of young people whose 'leading edge' members were born in 1982 and graduated high school in 2000. These are the young adults who began entering college, the military, and the workplace during the present decade, and who will continue to do so for perhaps another decade more. The Millennial generation has been exposed during their formative years to a unique variety of historical, cultural, economic, and technological changes that have shaped their particular attitudes and values, preferred social interaction styles, beliefs about what is proper in the workplace, and personal concerns and desires. Millennials are bringing their unique perspectives into their places of employment, where at times they clash with those of the older generations who are already established there.